IDEOMOTOR TRAINING AS A METHOD OF IMPROVING THE TECHNICAL SKILLS OF YOUNG BOXERS (Physical Culture and Sport: Scientific Perspective, 2025)
Ideomotor training, which is based on the imaginary reproduction of motor actions without their direct execution, is considered a promising direction in the system of sports training. The purpose of the study was to determine the effectiveness of using the ideomotor training method in the educational and training process of young boxers, aimed at improving the technical preparedness of athletes. Participants: 14 boxers, 15-16 years old, KZ DYUSSH№13, Kharkiv. Athletes were divided into a control (7 athletes) and an experimental (7 athletes) group randomly. The study was conducted during July and August 2025. The ideomotor training method was introduced into the training process of the experimental group, athletes in the control group performed passive stretching and breathing exercises without the use of imaginary movements. Research methods: theoretical analysis, method of testing technical elements (methods of testing technical readiness (number of direct hits on the bag with the right and left hand in 15 s; number of side hits on the bag with the right and left hand in 15 s), methods of mathematical statistics. Results: The implemented methodology provided for a phased mental reproduction of technical actions, which included the formation of motor images, sensory activation and modeling of competitive situations. Ideomotor exercises included short, imaginative and understandable instructions that combine a description of movements, sensations and the result. The wording was chosen in such a way as to evoke not only visual, but also kinetic and tactile associations in the athlete. As a result of the experiment, the level of performance of technical actions in the boxers of the experimental group was significantly higher than in the athletes of the control group, which indicates the effectiveness of the implemented training methodology (p
Keywords: boxing; ideomotor training; technical mastery; young boxers; technique